Health Problems and Illnesses: Overwhelming on Living Conditions of Elderly Individuals - Dr. Radhika Kapur, (International Journal of Preventive Medicine and Health (IJPMH), 2024)
The main objective of this research paper is to acquire an efficient understanding of various types of health problems and how they are overwhelming on living conditions of elderly individuals. The senior citizens are overwhelmed by different types of health problems and illnesses. These are experienced in a major or minor form. The senior citizens are required to be well-versed in terms of different types of methodologies and procedures, which would be facilitating in treating various types of health problems and illnesses. Within rural communities, the health care and medical facilities are not in a well-developed state, whereas, in urban communities, these are in a well-developed state. The senior citizens, migrate to urban communities in order to get their health problems and illnesses treated. As a consequence of promoting good health and well-being, the individuals in old age will render an important contribution in bringing about improvements in their overall quality of lives. The senior citizens in some cases are not ambulatory and are required to depend upon other individuals in order to take care of their needs and requirements. Hence, they are required to form cordial and amiable terms and relationships with other individuals, including family and community members. Hence, it is of utmost significance to take care of different types of health problems and illnesses. Therefore, it is understood on a comprehensive basis that health problems and illnesses are overwhelming on living conditions of elderly individuals. The main concepts that are taken into account in this research paper are, health problems and illnesses are overwhelming in old age, health issues in geriatrics, health issues among senior citizens and measures to be implemented in promoting good health and well-being.